Value-added Modeling and the Power of Magical Thinking - Braun, Henry (2012)
This article explains the impetus in the United States behind the drive to extend test-based accountability to teachers and the growing interest in employing value-added models to generate the indicators to be used in teacher evaluation. The empirical literature finds that teaching quality is the most important school-related determinant of student. Yet, in the main, teacher evaluations are done poorly – if at all – and compensation has been largely determined by seniority and credentials. Policy makers see strengthening teacher accountability as a priority. In particular, they are looking to increase the role of outputs in comparison to inputs. However, given the technical problems associated with status-based indicators of teacher and school effectiveness, the focus has turned to indicators based on some measure of the progress students have made during the academic year. Value-added analysis relies on sophisticated statistical models to generate estimates of the relative effectiveness of teachers, based on a measure related to student progress. This article provides a brief introduction to value-added models and summarizes key research findings. Although value-added estimates have some desirable properties, they do not represent a simple, neat solution to a complex evaluation problem. In this spirit, the article concludes by describing some of the many concerns regarding the use of value-added scores for high-stakes decisions and suggests some ways to enhance the likelihood that teacher accountability will contribute constructively to the improvement of teaching.